Utilization of Ict Tools in the Teaching-Learning Process by State Universities and Colleges in Caraga Region: Issues, Problems and Concerns - Christian A. Isip, Born; ., . (International Journal of Engineering and Technology, 2018)
Conceptually, the study is anchored in the so-called â€œblended learning frameworkâ€, a blend of learning theory, teaching practices and new technologies combined to provide students with rich, meaningful learning experiences that extend beyond the classrooms. The study was conducted in five (5) State Universities and Colleges (SUCs) in CARAGA Region. A Simple Random Sampling was employed both for faculty and student respondents. Frequency, percentage, and average were used to determine the descriptive interpretation of data collected in this study. This paper describes and identifies the common ICT tools used in the teaching and learning process.Â Â